2000
DOI: 10.1021/cm000298s
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction and X-ray Absorption Spectroscopy Studies of Sol−Gel-Processed Zirconium Titanates

Abstract: ZrTiO 4 samples were prepared by using a conventional hydrolytic alkoxide sol-gel route, a nonhydrolytic method, an acetic acid modified route, and by the direct reaction of the binary oxides. The local structure in the gels and its evolution upon heating was followed using EXAFS and XANES, and the crystallization of the products was examined using powder X-ray diffraction. All the solution-processed materials crystallized in the range 600-700 °C. The crystalline materials formed at 700 °C showed no evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 55 publications
3
26
0
2
Order By: Relevance
“…While on the XRD pattern of the Pd/TiO 2 catalyst, the crystalline structures were consistent with the anatase and rutile phases, the former phase was higher than the last one. The XRD pattern of the mixed ZT50 oxide showed broad diffraction lines consistent with an amorphous material as was reported previously [2,6,24] regardless the method of the synthesis. These behavior was associated to the formation of the mixed Zr-O-Ti bond that promotes the lost of crystalline phase on the mixed ZrO 2 -TiO 2 oxide, which reaches their maximum for the sample with equimolar composition as was demonstrated by molecular simulation [2].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…While on the XRD pattern of the Pd/TiO 2 catalyst, the crystalline structures were consistent with the anatase and rutile phases, the former phase was higher than the last one. The XRD pattern of the mixed ZT50 oxide showed broad diffraction lines consistent with an amorphous material as was reported previously [2,6,24] regardless the method of the synthesis. These behavior was associated to the formation of the mixed Zr-O-Ti bond that promotes the lost of crystalline phase on the mixed ZrO 2 -TiO 2 oxide, which reaches their maximum for the sample with equimolar composition as was demonstrated by molecular simulation [2].…”
Section: Resultssupporting
confidence: 84%
“…These behavior was associated to the formation of the mixed Zr-O-Ti bond that promotes the lost of crystalline phase on the mixed ZrO 2 -TiO 2 oxide, which reaches their maximum for the sample with equimolar composition as was demonstrated by molecular simulation [2]. However, crystallization of amorphous ZT50 oxide to ZrTiO 4 phase is reported above 600°C [24][25][26][27]. Figure 3a, shows the TEM image of a Pd nanoparticle on the surface of the mixed ZT50 oxide.…”
Section: Resultsmentioning
confidence: 80%
“…A higher variation was observed in the a and b parameters. Xu et al [15] reported also a higher alteration in the a and b parameters and McHale [16] attributed the variation in the parameter b to the degree of cation ordering in ZrTiO 4 .…”
Section: Resultsmentioning
confidence: 96%
“…5b) gave first coordination sphere correspondent to Zr-O bonding, but the second coordination sphere around 3.4 Å was obscure. In the previous report about EXAFS experiments on low-crystalline ZrO 2 gel samples using synchrotron light source, the EXAFS spectra, which is recorded in the k-range of 1-17 Å -1 , showed the weak second coordination sphere correspondent to Zr-Zr in the RSF clearly [45]. In this experiment, because the X-ray source was an X-ray tube with a W target, the EXAFS spectrum of higher k-range than 12 Å -1 was not clear and the second coordination in the RSF was obscure.…”
Section: Local Structure Around Zirconium Of a Zr-mgal-ht Samplementioning
confidence: 85%